TINGKAT KECUKUPAN ZAT GIZI, AKTIVITAS FISIK, DAN KEBUGARAN KARDIORESPIRATORI PEGAWAI PT. INDOCEMENT BOGOR - Tamimi, Kharisma; Rimbawan, Rimbawan (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2015)
ABSTRACTThe general objective of this study was to analyse nutritional adequacy, physical activity, and cardiorespiratory fitness among Indocement’s workers at Bogor. The cross-sectional study was applied with purposive sampling, involving 32 office workers and 32 plant workers. Most of subjects (59.4% and 78.2%) had a normal Body Mass Index (BMI). The mean VO2 max of plant workers (24.4±7.6 mL/kg/mnt) was higher than office workers (22.9±7.5 mL/kg/mnt). There were no differences of macrocutrients adequacy (energy, protein, fat, and carbohydrate) between two workers (p>0.05). Physical activity level of plant workers was higher than the office workers, and it was categorized as moderately active (59.4%), whereas the office workers categorized as sedentary (75.0%). The office workers had better exercise (160.3±118.0 minutes) than the plant workers (89.1±167.6 minutes). Moreover, there were differences on physical activity and habitual exercise between the two groups (p<0.05). The significant correlations between age, physical activity, and habitual exercise with VO2 max were found on plant workers (p<0.05), but not on office workers (p>0.05).Keywords: cardiorespiratory fitness, nutritional adequacy, physical activityABSTRAKTujuan penelitian ini adalah untuk menganalisis tingkat kecukupan gizi, aktivitas fisik, dan tingkat kebugaran kardiorespiratori pegawai PT. Indocement di Bogor. Desain penelitian adalah cross-sectional dengan purposive sampling, melibatkan 32 pegawai kantor dan 32 pegawai lapang PT. Indocement. Sebanyak 59,4% pegawai kantor dan 78,2% pegawai lapang memiliki IMT yang normal. Rata-rata VO2 max kelompok lapang (24,4±7,6 mL/kg/menit) lebih tinggi dibandingkan kelompok kantor (22,9±7,5 mL/kg/menit). Tingkat kecukupan zat gizi kedua kelompok tidak berbeda (p>0,05). Sebagian besar (59,4%) pegawai kelompok lapang mempunyai kategori aktivitas sedang dan sebanyak 75,0% kelompok kantor mempunyai kategori aktivitas fisik ringan. Kebiasaan olahraga kelompok kantor lebih baik (160,3±118,0 menit) dibandingkan kelompok lapang (89,1±167,6 menit). Terdapat perbedaan aktivitas fisik dan kebiasaan olahraga antara kelompok kantor dan lapang (p<0,05). Terdapat hubungan yang signifikan antara usia, kebiasaan olahraga, dan aktivitas fisik dengan VO2 max pada kelompok lapang (p<0,05), dan tidak terdapat hubungan pada kelompok kantor (p>0,05).Kata kunci: aktivitas fisik, kebugaran kardiorespiratori, tingkat kecukupan zat gizi